Identification of musical talents: validity indices of the Protocol for Screening Musical Abilities (Orfeu, 2026)
The objective of this study was to present the validity indexes of the Protocol for Screening Musical Abilities (PSHM). It was based on the psychophysical method of paired comparison with descriptive and non-parametric analysis. Ten schools participated (public, private, indigenous, one talent center in Brazil and another one in Mexico - 563 students aged 6 to 12. Results: i) the binomial analysis showed a significant association (p
Keywords: Musical Education; Special Education; Talent Identification; Music Aptitude